Analysis and treatment of a type of 110‐kV transformer with insulation resistance decline defect. Issue 11 (24th July 2019) - Zhang, Li; Su, Wei; Qian, Yihua; Chen, Tiansheng; Fan, Shengping; Fu, Qiang; Zhao, Yaohong; Zhu, Zhiping; Wang, Deng
Abstract : Recently, a kind of 110‐kV transformer resistance decline defect was found during our routine preventive test of transformers in the Guangdong power grid. The number of defective transformers reached thirty. This phenomenon seriously threatened the safe and steady operation of the power grid. The analysis and treatment of this resistance decline defect were carried out. The key reason for this defect was confirmed. The insulating characteristics of insulating oil decreased. Aminopyrine is a kind of medicine used as an antipyretic analgesic. However, it was seldom investigated by the electric power industry. Aminopyrine as a potential contaminant was found to be present in insulating oils of transformers causing insulation resistance decline defect. Herein, the analysis process of defective insulating oils was introduced. The determination and quantitative detection of aminopyrine were performed using a gas chromatography‐mass spectrometer, in which the highest concentration of aminopyrine in insulating oil was determined to be nearly 100 mg/kg. The source of aminopyrine was surveyed. Moreover, the impact mechanism between aminopyrine and insulating property of transformer oil was discussed. Finally, we found adsorption was effective for this defect. To date, this method has been applied to solve this defect in the Guangdong power grid. © 2019 Institute of Electrical Engineers of Japan. Published by John Wiley & Sons, Inc.